Applied computational intelligence : (World Scientific, 2004)
FLINS, originally an acronym for "Fuzzy Logic and Intelligent technologies in Nuclear Science", has now been extended to include computational intelligent systems for applied research. FLINS 2004, is the sixth in a series of international conferences, covers state-of-the-art research and development in applied computational intelligence for applied research in general and for power/nuclear engineering in particular. This book presents the latest research trends and future research directions in the field.